The Effectiveness of Website-Assisted Learning Multimedia to Improve Mathematics Learning Achievement of Elementary School Students - Satriani, Rafika Dewi; Prasojo, Lantip Diat (Journal of Integrated Elementary Education, 2024)
This study aims to determine the effectiveness of web-assisted learning multimedia in improving Maths learning achievement among primary school students. This study used a quasi-experimental approach, using a pre-test and post-test design to measure students' learning achievement. Data collection was conducted using test instruments designed to assess learning outcomes in a structured and objective manner. The effectiveness of the web-based multimedia intervention was measured through the Normalised Gain (N-Gain) test, which evaluates the level of improvement in students' mathematics learning achievement. Differences in the dependent variable between the experimental and control groups were further analysed using Paired Samples t-test and Independent t-test. The results of the N-Gain test indicated that the experimental group showed significantly greater improvement in Mathematics learning achievement compared to the control group, with the experimental group achieving a medium category N-Gain score of 0.68, while the control group's score was categorised as low at 0.17. In addition, the Paired Samples t-test and Independent t-test showed significance levels below 0.05, further validating the substantial impact of the web-based multimedia on student achievement. These findings underscore the potential of web-based multimedia as an effective instructional tool to improve students' learning achievement, especially in the area of Mathematics. This research contributes to the growing body of knowledge in educational technology and offers practical insights to enhance the learning process among young learners